2021
DOI: 10.1021/acsami.0c22047
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Neurotransmitter Activity and Realizing Algebraic Arithmetic on Flexible Protein-Gated Oxide Neuromorphic Transistors

Abstract: Recently, flexible neuromorphic devices have attracted extensive attention for the construction of perception cognitive systems with the ultimate objective to achieve robust computation, efficient learning, and adaptability to evolutionary changes. In particular, the design of flexible neuromorphic devices with data processing and arithmetic capabilities is highly desirable for wearable cognitive platforms. Here, an albumen-based protein-gated flexible indium tin oxide (ITO) ionotronic neuromorphic transistor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…So far, various materials have been adopted to fabricate optoelectronic synaptic transistors [ 96 , 101–104 ], including oxide semiconductor, 2D-layered semiconductor, organic semiconductor, environmentally friendly biomaterials, carbon nanotubes (CNTs), quantum dots (QDs) and ionic gel electrolytes. In addition, various novel structures have also been developed to fabricate optoelectronic devices.…”
Section: Artificial Perception System Based On Neuromorphic Transistorsmentioning
confidence: 99%
“…So far, various materials have been adopted to fabricate optoelectronic synaptic transistors [ 96 , 101–104 ], including oxide semiconductor, 2D-layered semiconductor, organic semiconductor, environmentally friendly biomaterials, carbon nanotubes (CNTs), quantum dots (QDs) and ionic gel electrolytes. In addition, various novel structures have also been developed to fabricate optoelectronic devices.…”
Section: Artificial Perception System Based On Neuromorphic Transistorsmentioning
confidence: 99%
“…Thus, it is of great significance to realize information decoding and processing on neuromorphic devices, which can expand their application in artificial neural networks, natural language processing, human-computer interface, etc. Previously, we have demonstrated algebraic arithmetic 12 and binary code compilation under the ASCII code 56 on oxide neuromorphic transistors. Here, we conceptually demonstrate information decoding on the proposed ITO photoelectric neuromorphic transistor, as schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several kinds of neuromorphic devices have been proposed, including two-terminal memristors [5][6][7] and three-terminal transistors. [8][9][10][11][12][13][14] Additionally, multi-terminal memristors and memtransistors have also been proposed, resulting in the emulation of advanced synaptic functions, including synaptic competition and synaptic cooperation, heterosynaptic plasticity, etc. [15][16][17] Moreover, advanced neural functions have also been mimicked, including image memory, 11,18 pattern recognition, 19 reservoir computation, 20 classical conditioned reflex, 21,22 etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 257 ] In a recent study, in which a learning mechanism was created as a synaptic device, albumen (the part of the egg that contains albumin) was turned into an electrolyte, and proton conductivity was increased so that it could be used in artificial nerve applications. [ 258 ] It was reported that the rate of switching on and off currents was relatively high in transistors containing albumin protein (>10 7 ). A table of performances of flexible transistors is given in Table 4 .…”
Section: Sustainable Materials In Flexible Electronicsmentioning
confidence: 99%